A comparison of the effects of two types of periodontal dressings with and without zinc oxide on non-surgical periodontal treatment - Nguyen, Thi Thuy Duong; Tran, Khanh Hung (Tạp chí Y Dược Huế, 2025)
Background: Periodontal dressings have recently become an important research topic in periodontal treatment. Periodontal dressings have also proven effective in supporting non-surgical mechanical therapy for short-term clinical outcomes. Objective: This study evaluated the effects of two types of periodontal dressings, with and without zinc oxide, on non-surgical periodontal treatment. Materials and Methods: This randomized controlled trial, with a split-mouth design, was conducted on 31 patients with stage II-III periodontitis (AAP/EFP 2017). After scaling and root planing, two types of periodontal dressings were applied in opposite sextant regions. Clinical periodontal indices were assessed at baseline and 1 week, 1 month, 3 months, and 6 months after treatment. Radiographs were obtained at baseline and 6 months after treatment. Results: After treatment, the plaque index (PlI), bleeding on probing index (BOP), probing pocket depth (PPD), and clinical attachment level (CAL) in both groups were significantly reduced compared with baseline values. The periodontal dressing without zinc oxide showed higher effects than periodontal dressing with zinc oxide in terms of changes in the gingival index (GI), PPD, and CAL. Conclusion: Periodontal dressings, especially without zinc oxide, support clinical improvement in stage II-III periodontitis through non-surgical therapy.